A Flux Weakening Control Algorithm Based on Notch Filter - Yu Jiabin; Wang Xiaoyi; Xu Jiping; Qin Xiaofei; Zheng Jun (Institute of Advanced Engineering and Science, 2014)
In order to solve the problem that the SVPWM over modulation caused the fluctuation of steady-state speed in the flux weakening region of surface-mounted permanent magnet synchronous motor (PMSM), by analyzing the mechanism of the leading angle flux weakening control algorithm, the conclusion is that the sixth harmonic of inverter output voltage caused by SVPWM over modulation which is transmitted to the d-q reference currents through the flux weakening voltage close-loop deteriorates the current and speed control performance. A notch filter is designed in the voltage close-loop to filter the sixth harmonic component of the input voltage signal, meanwhile the other signal components are not affected. The experiment results show that, after adding notch filter, the sixth harmonic component of the input voltage signal is significantly reduced and the current waveforms are remarkably improved, so that the flux weakening speed control performance is effectively enhanced.